Conservation logics that reshape mega-event spaces: San Antonio and Brisbane post expo. (2nd September 2020) - Minner, Jennifer; Abbott, Martin
ABSTRACT: International expositions (expos) are significant to the history of urban planning. Analysis of post-event urban spaces can provide valuable insights into the study of spatial planning, parks planning, and heritage conservation. Case studies, conducted at two former expo sites in the US and Australia focus on the role of retention, reuse, heritage, and parks conservation as forces shaping urban spaces over time. The first case at the site of Hemisfair '68, in San Antonio, Texas, traces the role of urban renewal and conservation in the history of the site. In contemporary planning efforts, modernist pavilions from Hemisfair '68 join nineteenth century buildings as remnants of history that raise questions for the area envisioned as a New Urbanist neighbourhood. The second case study, a former industrial district was cleared and a working-class precinct transformed for Expo 88, in Brisbane, Queensland. The site was later redeveloped into the South Bank Parklands. Over time, South Bank evolved through redevelopment and master planning, public outcry, and instances of conservation in and around the expo site. Common to both cases is the conservation of parks, iconic and ordinary buildings, and public art, which are the outcome of individual and collective actions to shape urban landscapes.